(untitled) (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2026)
Electric motors are a must-have in today’s high-performance electric drive landscape. They inevitably involve dynamic processes and, as a result, electrodynamic, magnetic, mechanical, and thermal stresses that can affect their lifespan. Dedicated design, based on modeling and simulation, is becoming a hot topic in research.